Invited Paper: Illuminating the Value of Larger Color Gamuts for Quantum Dot Displays. Issue 1 (June 2014) - Van Derlofske, John F.; Hillis, James M.; Lathrop, Art; Wheatley, John; Thielen, James; Benoit, Gilles
Abstract Quantum dot technology offers the promise of efficient and relatively inexpensive liquid crystal displays (LCDs) with large color gamuts (∼115% NTSC u'v'). Now, for the first time, a variety of high color performance devices are on the immediate horizon for applications ranging from 3" diagonal hand held smart phones to +85" diagonal TVs . While people clearly prefer color displays, the relative value of different color reproduction systems remains an open question. Here we review how quantum dots enable high color performance and some of the advantages of large color gamut displays.